Vocational Training in Peñascal Kooperatiba (Journal of Parents and Teachers, 2021)
Peñascal kooperatiba is a social initiative entity with more than 30 years of experience. Throughout this time, it has developed a singular vocational training model that transcends academia, offering comprehensive training, with a systematized teaching-learning proposal and with which it achieves that its students, with low professional qualifications, reach a positive position in the face of training, achieve the objectives proposed in the curricula, improving their employability and their possibilities of social inclusion.
Keywords: cooperative learning; experiential learning; vocational training; holistic approach; social integration; continuous assessment